A New View Duchenne Muscular Dystrophy (Global Journal of Science Frontier Research, 2021)
Duchenne Muscular Dystrophy is the result of mutation gene-dystrophine, productprotein-dystrophin presents in organism as the complexes proteins placing everywhere, their role unclear. Suppose all dystrophine complexes work as one functional System D, thanks signal ability complexes. Suppose the System D the ancient and appeared when the gene dystrophin-utrophin divided into two genes dystrophin and utrophin at early vertebrates. Perfect this System made the gene the longest in human genome. The surprising activity creat inkinase-21-23 000 ME, found by author, make to think of the damage much membranesdamage System. Destroy System D is beginning of the disease, finishing apoptosis-general destructive factor. Two factors determinate the disease-damage the system D and apoptosis.
Keywords: dystrophin; creatine kinase; metabolism; apoptosis